Genetic characterization of phenicol-resistant Escherichia coli and role of wild-type repressor/regulator gene (acrR) on phenicol resistance - Yaqoob, Muhammad; Wang, Li Ping; Kashif, Jam; Memon, Javed; Umar, Sajid; Iqbal, Muhammad Farooq; Fiaz, Muhammad; Lu, Cheng-Ping (Folia microbiologica, 2018)
The genetic basis for phenicol resistance was examined in 38 phenicol-resistant clinical Escherichia coli isolates from poultry. Out of 62 isolates, 38 showed resistance for chloramphenicol and nine for florfenicol, respectively. Each strain also demonstrated resistance to a variety of other antibiotics. Molecular detection revealed that the incidence rates of the cat1, cat2, flo, flo-R, cmlA, and cmlB were 32, 29, 18, 13, 0, and 0%, respectively. Nineteen strains were tolerant to organic solvents. PCR amplification of the complete acrR (regulator/repressor) gene of five isolates revealed the amino acid changes in four isolates. DNA sequencing showed the non-synonymous mutations which change the amino acid, silent mutation, and nucleotide deletion in four isolates. MY09C10 showed neither deletion nor mutation in nucleotide. The AcrA protein of the AcrAB multidrug efflux pump was overexpressed in these strains. Complementation with a plasmid-borne wild-type acrR gene reduced the expression level of AcrA protein in the mutants and partially restored antibiotic susceptibility one- to fourfold. This study shows that mutations in acrR are an additional genetic basis for phenicol resistance.
Keywords: mutace; kur domácí; Animals; Gene Expression Regulation, Bacterial; testy genetické komplementace; Genotype; acrR mutation; mikrobiální testy citlivosti; Repressor Proteins; Escherichia coli; Chickens; represorové proteiny; DNA bakterií; Membrane Transport Proteins; bakteriální geny; Poultry Diseases; membránové transportní proteiny; DNA, Bacterial; Phenicol; genotyp; nemoci drůbeže; Anti-Bacterial Agents; Genetic Complementation Test; Mutation; Chloramphenicol Resistance; proteiny z Escherichia coli; regulace genové exprese u bakterií; Complementation; Microbial Sensitivity Tests; rezistence na chloramfenikol; mnohočetná bakteriální léková rezistence; Drug Resistance, Multiple, Bacterial; Genes, Bacterial; zvířata; antibakteriální látky; AcrAB efflux pump; Escherichia coli Proteins